Civil Society and the Professions in Eastern Europe - Sokolowski, S. Wojciech. author. aut Link
XVI, 260 p.
Keywords: Focusing on service-providing organizations established by health and human service professionals in post-Communist Poland, this book adds a new dimension to the sociological study of voluntary organizations. The author investigates the motives and interests of the people who establish these organizations and the connections among organizational forms, the social organizations of production, and the occupational interests of professional service providers.